Nutrition and Labor Producvivity in Agriculture: Estimates for Rural South India - Deolalikar, Anil B. (The Review of Economics and Statistics, 1988)
Using panel data for rural South India, a fixed-effects individual wage equation and farm production function are estimated that have calorie intake and nutritional status (weight-for-height) of workers as their arguments. Neither market wages, nor farm output, are observed to be responsive to changes in the daily energy intake of workers. However, both are highly elastic with respect to weight-for-height. These results suggest that, while the human body can adapt to inadequate nutrition in the short run, it cannot adapt as readily to chronic malnutrition that eventually results in loss of weight-for-height. Copyright 1988 by MIT Press.